The Institute of State Gendarmerie in the System of Public Order Protection Bodies of the Western Ukrainian People’s Republic (November 1918 – June 1919) - Ukhach , Vasyl (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The aim of this article is to analyze the process of establishing the State Gendarmerie within the system of public order protection bodies of the Western Ukrainian People’s Republic during the period from November 1918 to June 1919. The research methodology is based on the principles of historicism, scientism, objectivity, and systematicity. Methods of analysis and synthesis, generalization, and historical-comparative approaches were applied to study the organizational and legal framework, peculiarities of formation, and practical activities of one of the key structures in the law enforcement system of the young republic – the State Gendarmerie. Scientific novelty. Based on published sources and historiographic research, the article examines the organizational and legal foundations of the establishment of the institute and structures of the State Gendarmerie of the WUPR in the law enforcement system during the early period of state functioning, from November 1918 to June 1919. The article provides a detailed analysis of the law on the State Gendarmerie, its quantitative membership, leadership bodies, functions, duties, and responsibilities. It also presents statistical data on the personnel and territorial composition of the service, requirements for candidates, and the social benefits for gendarmerie officers. The results of the study indicate that the legislative basis for the creation and development of the State Gendarmerie was rooted in Austro-Hungarian law, which did not contradict the interests of the Ukrainian state. Documents show the consistency and purposeful nature of the formation and establishment of the public order protection system, and the State Gendarmerie in particular, within the broader context of the state-building trends of the WUPR. After the units of the Ukrainian Galician Army (UGA) crossed the Zbruch River, the State Gendarmerie was subordinated to the Rear Command and thus ceased to perform public order functions within the state, acting solely as a part of the Armed Forces.